The Influence of the Teaching Style of Communication on the Motivation of Students to Learn Foreign Languages - Marina Ivanova; Natalia Shlenskaya; Natalia Mekeko; Tatiana Kashkarova (National Research University Higher School of Economics, 2019)
Nowadays, when the role of knowing foreign languages is extremely high and the demand for specialists who are proficient in a language is continuing to increase, we face the problem of a lack of desire to learn foreign languages among non-linguistic majors. We supposed that the type of teacher-student interaction style (authoritarian, democratic, and liberal) could influence students' motivation type (internal, external positive, external negative, or amotivation) and this was the aim of the study. We surveyed 230 second-year students of the intramural form of study seeking a baccalaureate degree from Moscow State University of Food Production. Among the respondents there were 143 girls and 87 boys aged 18-20, citizens of the Russian Federation. The experiment was divided into three stages and it took three semesters to complete the study. The aim of the first stage was to investigate students' preferences related to teacher-student interaction style, and the prevailing type of learning motivation to study and to learn foreign languages. The second stage of the study was aimed to investigate how teacher-student interaction style influences the nature and type of students' motivation to learn. In the last stage of the study, the output testing of student performance was implemented and all the results from the previous stages were compared and analyzed. The results of the experiment clearly demonstrated that both authoritarian and democratic teacher-student interaction styles could have a positive influence on students' educational behaviour and academic performances while the implementation of the liberal teacher-student interaction style led to amotivation. At the same time, the democratic style, contrary to the authors' hypothesis, predominantly provoked external motivation, while an authoritarian style significantly activated internal motivation.